Efeito antinociceptivo e anti-inflamatório do alcalóide aporfínico estefalagina em um modelo de gota em camundongos - Santos, Priscilla Dias (2021)
Gout is an inflammatory disease characterized by the accumulation of monosodium urate crystals (MSU) in the joints, which causes severe pain and inflammation in the affected area. The drugs most used to treat the disease have many contraindications, mainly related to comorbidities, therefore, there is a need to find new and more effective ways. A widely studied line is that of natural products, several medications have already been produced from this source, such as colchicine, an alkaloid used to treat gout. Alkaloids are compounds already known in the literature for having bioactive actions, such as antinociception and anti-inflammation. Therefore, the aim of this study was to evaluate the antinociceptive and anti-inflammatory effect of the aporphine alkaloid stephalagine extracted from Annona crassiflora mart. Stephalagine (1 mg/kg) had a significant antinociceptive effect (by Von Frey test) when compared to the group that received the intra-articular injection of MSU (100 µg/joint) in 2, 4 and 6 h after application. Stephalagine was also able to significantly reduce the presence of the myeloperoxidase enzyme in the joint tissues of the mice when compared to the group that received only MSU. In addition, tests were carried out to assess the toxicity of the alkaloid. The stephalagine was not able to alter the presence of the enzymes AST and ALT in the bloodstream or the compounds urea and creatinine. It was also observed for 7 days if the compound causes any macroscopic changes in the mice, such as sudden changes in weight, deformations, changes in the coat, in the feces and none of this was seen. Therefore, it is observed that stephalagine may be an alternative for the treatment of gout, since it was able to have antinociceptive and anti-inflammatory effects and no toxic/side effects.